Promoting Prosocial Beliefs And Behavior Toward People With Disabilities In Nepal Through A Children’s Entertainment-Education Program - William J Brown; Deborah A Strong (Disability, CBR and Inclusive Development)
Purpose This quasi-experimental field study examines the prosocial influences of a children's entertainment-education television programme, Khushi Ko Sansar, on children’s beliefs and intended behaviour towards people with disabilities in Nepal. Method Pre-test and post-test survey data were gathered from 357 Nepali children from nine communities that took part in the study. The children were shown two television episodes in which the star of the programmes, a dog named Khush, befriends and visits people with disabilities. Results Post-test results show that children developed strong identification with Khush and adopted his prosocial beliefs and behaviour towards people with disabilities. Conclusions The authors conclude that the entertainment-education television programme, Khushi Ko Sansar, provided a positive role model for children who encounter people with disabilities. Implications of these findings suggest that entertainment-education media can improve the treatment of people with disabilities and can promote beneficial health beliefs and practices. Key words: Children’s television, entertainment-education, Nepal, people with disabilities, role models doi 10.5463/DCID.v22i2.33